Rhinofacial conidiobolomycosis mimicking facial cellulitis: a diagnostic challenge in an immunocompromised man - Masri, Siti Norbaya; Amin Nordin, Syafinaz; Jamalut, Yusanita; Mustakim, Sahlawati; Zaini, Adilahtul Bushro; Tan, Xue Ting; Mohd-hatta, Nurfareha (Fakulti Perubatan dan Sains Kesihatan, UPM, 2024)
Conidiobolomycosis is a fungal infection caused by Conidiobolus spp. Common symptoms include epistaxis, nasal discharge, nasal obstruction, sinus tenderness, and persistent extensive facial swelling leading to facial mutilation. Our case describes an indolent presentation of conidiobolomycosis in an immunocompromised young man, resulting in delayed diagnosis and treatment. A 29-year-old Malay gentleman, a chef, who was hearing disabled and on anti-tuberculosis treatment, presented with a five-month history of unwellness, poor oral intake, and painless left nasal cavity swelling. Despite classic symptoms of conidiobolomycosis being absent, biopsy and PCR confirmed Conidiobolus megalotocus. After antifungal treatment initiation, his condition significantly improved, with resolution of facial swelling, after two months. This case highlights the importance of considering conidiobolomycosis in immunocompromised patients even with atypical presentations.